Predicción del riesgo a la salud infantil en una zona contaminada por plomo - Villalobos Jáuregui, A.; Valdez Perezgasga, F.; García Vargas, G. G.; Alonso Chamarro, J. (Revista Mexicana de Ingenieria Biomedica, 2006)
The content of lead in soil within a 2.8 Km radius around the largest non ferrous smelter in Latin America has been investigated. The dispersion of lead within this area was assessed using a geographic information system. These results were used to predict lead blood levels of children living in the city of Torreon where the smelter is located. Although other metals were also present in the samples, particular attention was given to lead as it may cause various deleterious effects to the health of those exposed. In particular, lead is damaging to the neurological development of children. The results of lead levels in soil and the risk of lead levels in the blood of children are a useful tool for environmental and health authorities and for citizens at large to appraise the effectiveness of cleaning up efforts, to evaluate health risks and to adopt effective preventive measurements.